Partial-Duplex Amplify-and-Forward Relaying: Spectral Efficiency Analysis under Self-Interference - R. López-Valcarce; C. Mosquera (IEEE Transactions on Wireless Communications, 2019)
We propose a novel mode of operation for Amplify-and- Forward relays in which the spectra of the relay input and output signals partially overlap. This partial-duplex relaying mode encompasses half- and full-duplex as particular cases. By viewing the partial-duplex relay as a bandwidth-preserving Linear Periodically Time-Varying system, a spectral efficiency analysis under self-interference is developed. In contrast with previous works, self-interference is regarded as a useful informationbearing component rather than simply assimilated to noise. This approach reveals that previous results regarding the impact of self-interference on (full-duplex) relay performance are overly pessimistic. Based on a frequency-domain interpretation of the effect of self-interference, a number of suboptimal decoding architectures at the destination node are also discussed. It is found that the partial-duplex relaying mode may provide an attractive tradeoff between spectral efficiency and receiver complexity.
Keywords: full-duplex; myrada; winter